Efficient high-power femtosecond Yb3+:KY(WO4)2 laser. (26th June 2015) - Kovalyov, A A; Preobrazhenskii, V V; Putyato, M A; Rubtsova, N N; Semyagin, B R; Kisel, V E; Rudenkov, A S; Kuleshov, N V; Pavlyuk, A A
Abstract: A stable mode-locking regime at a repetition rate of 70 MHz with 5 W average power, maximum output pulse energy of about 71 nJ, and pulse duration of 114 fs were obtained in an Yb :KY(WO4 )2 laser with longitudinal 'off-axis' diode pumping. Optical-to-optical laser efficiency was as high as 33.3%. A semiconductor saturable absorber including quantum wells with nanostructured barriers was designed and manufactured for this laser.